Development of application of self-help skills for children with intellectual disability in a wetland environment - Wulandari, Rona; Eviani Damastuti; Imam Yuwono; Utomo Utomo; Siti Jaleha; Dewi Rizka Adelia; Siti Nur Sabah (Universitas Negeri Yogyakarta, 2025)
The limited ability to think in children with intellectual disabilities has an impact on their understanding of danger and personal safety. Children with intellectual disabilities need to be taught to recognize and help themselves from the dangers found in the surrounding environment. The purpose of this study was to develop an application of self-help skills for children with intellectual disabilities in a wetland environment. Using the Research and Development (R&D) method within the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study was conducted at State Special Needs School 3 in Banjarmasin. Data were collected through tests, interviews, and documentation, and analyzed both qualitatively and quantitatively. The resulting application features four main menus: self-help during floods, fires, electrical short circuits, and encounters with wild animals. Each menu includes instructional videos outlining hazards and safety procedures. The application significantly improved participants' understanding, with post-test scores (1.480) surpassing pre-test results (1.130). Further research is recommended to evaluate the effectiveness of the application in fostering independence among children with intellectual disabilities.